2020
DOI: 10.1111/pce.13727
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione‐dependent denitrosation of GSNOR1 promotes oxidative signalling downstream of H2O2

Abstract: Photorespiratory hydrogen peroxide (H2O2) plays key roles in pathogenesis responses by triggering the salicylic acid (SA) pathway in Arabidopsis. However, factors linking intracellular H2O2 to activation of the SA pathway remain elusive. In this work, the catalase‐deficient Arabidopsis mutant, cat2, was exploited to elucidate the impact of S‐nitrosoglutathione reductase 1 (GSNOR1) on H2O2‐dependent signalling pathways. Introducing the gsnor1‐3 mutation into the cat2 background increased S‐nitrosothiol levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…Furthermore, the GSNOR enzyme is posttranslationally activated by direct denitrosylation in a GSH-dependent manner. Activation of ICS expression leads to SA accumulation [100]. In summary, the ROS and NO formation during plant defense modulate the GSH/GSSG ratio and ultimately increase GSH levels in resistant plants.…”
Section: Gsh and Samentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the GSNOR enzyme is posttranslationally activated by direct denitrosylation in a GSH-dependent manner. Activation of ICS expression leads to SA accumulation [100]. In summary, the ROS and NO formation during plant defense modulate the GSH/GSSG ratio and ultimately increase GSH levels in resistant plants.…”
Section: Gsh and Samentioning
confidence: 99%
“…Conversely, increased AtGSNOR1 activity reduces protein-SNO formation and positively regulates the SA induced defense responses [99]. Others have recently shown that the activation of GSNOR1 enzyme leads to the release of inhibition of ICS expression in the presence of H 2 O 2 [100]. However, when GSNOR1 is inactive, the accumulation of GSNO leads to the inhibition of ICS expression.…”
Section: Gsh and Samentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely documented that salicylic acid (SA) plays an essential role in plant resistance to biotrophic and semibiotrophic pathogens such as the model pathogen Pseudomonas syringae pv. tomato DC3000 (Pst DC3000) (Chen et al, 2020a;Peng et al, 2021;Zhang et al, 2020c).…”
mentioning
confidence: 99%